2012
DOI: 10.1007/s10764-012-9623-2
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Change of Social Relationship Quality in Captive Chimpanzees (Pan troglodytes)

Abstract: In social animals an individual's fitness depends partly on the quality of relationships with others. Qualitative variation in relationships has been conceptualized according to a three-dimensional structure, consisting of relationship value, compatibility, and security. However, the determinants of the components and their temporal stability are not well understood. We studied relationship quality in a newly formed group of 20 captive chimpanzees made up of several previously existing social groups. We assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 53 publications
8
51
1
Order By: Relevance
“…Similar to recent studies from the wild (e.g., Foerster et al, ; Lehmann & Boesch, ) and captivity (e.g., Fraser et al, ; Koski et al, ) we found evidence for durability of grooming patterns between chimpanzee females. They showed consistency between adjacent periods, but females shifted partner preferences between the unstable and stable periods, which were 4 years apart.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to recent studies from the wild (e.g., Foerster et al, ; Lehmann & Boesch, ) and captivity (e.g., Fraser et al, ; Koski et al, ) we found evidence for durability of grooming patterns between chimpanzee females. They showed consistency between adjacent periods, but females shifted partner preferences between the unstable and stable periods, which were 4 years apart.…”
Section: Discussionsupporting
confidence: 91%
“…Two earlier studies have explored the effect of rank reversals in the male hierarchy on relationships within a primate group (de Waal, ; Perry, ) but none so far have explicitly considered the impact of social uncertainty on the durability of affiliation patterns in non‐human primates, and the role of social uncertainty on the durability of human social relationships is poorly understood (Bukowski, Newcomb, & Hartup, ). Chimpanzees ( Pan troglodytes ) are a suitable species to examine the role of social uncertainty on the durability of affiliation patterns as enduring affiliation patterns have been reported between males and females (Gilby & Wrangham, ; Langergraber, Mitani, & Vigilant, ; Lehmann & Boesch, ; Koski, de Vries, van de Kraats, & Sterck, ; Mitani, ), and males are known to engage in flexible social interactions which may depend on social uncertainty (e.g., Nishida, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have noted that sex differences are influenced by captivity. In zoo chimpanzees, both males and females establish stable, high quality relationships (de Waal 1984, 1994; Fraser et al 2008; Koski et al 2012) which may account for the lack of difference in grooming network positions in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Accordingly, siblings always formed significantly stronger relationships compared to unfamiliar individuals (whenever the group comprised unfamiliar individuals: A and B), and to familiar partners in the parent‐ (A) and hand‐raised (C) groups. However, kin are not always the preferential partners (e.g., Lukas, Reynolds, Boesch, & Vigilant, ; Wittemyer et al, ) and beside relatedness, familiarity often plays a major role on grouping patterns and social preferences (e.g., Griffiths, Brockmark, Höjesjö, & Johnsson, ; Koski, Vries, Kraats, & Sterck, ). Depending on the nature of past interactions, familiarity can increase partners’ propensity to reciprocate interactions (Brosnan & de Waal, ), acting as a feedback loop securing valuable relationships (in primates: Seyfarth & Cheney, ; Barrett, Henzi, Weingrill, Lycett, & Hill, ; Tiddi, Aureli, Polizzi Di Sorrentino, Janson, & Schino, ; in birds: Krams, Krama, & Igaune, ; Wheatcroft & Price, ).…”
Section: Discussionmentioning
confidence: 99%